Influence of the ripening stage and the lyophilization of wild cardoon flowers on their chemical composition, enzymatic activities of extracts and technological properties of cheese curds. (15th April 2018) - Ben Amira, Amal; Blecker, Christophe; Richel, Aurore; Arias, Anthony Argüelles; Fickers, Patrick; Francis, Frédéric; Besbes, Souhail; Attia, Hamadi
Highlights: Cardoon flowers were collected at two ripening stages (A and B). Chemical composition of the two flowers batches was studied. Enzymatic activities (MCA and PA) of extracts were investigated. Technological properties of C. cardunculus curds were compared with chymosin curd. Lyophilized flowers (A) produced coagulant with better clotting properties. Abstract: The selection of an appropriate Cynara cardunculus flowers batch is a preliminary step to produce rennet with better clotting properties. For this reason, we proposed to study the influence of the ripening stage and the lyophilization of cardoon flowers on their chemical composition, enzymatic activities of extracts, and technological properties of cheese curds. Results of flowers composition have shown that lyophilized flowers harvested at the middle of ripening stage (A) could be employed to produce mainly proteins or milk-clotting proteases. To confirm this, enzymatic activities of extracts and technological properties of curds were assessed. The experimental findings revealed that flowers lyophilization seems to be an efficient way to produce rennet with better clotting properties, leading to higher yield, moisture, and texture parameters of curd. These findings allowed us to select lyophilized flowers (A) for further cheese making process.